Hubungan Pemberian Mp-Asi Pada Bayi Usia 0-6 Bulan Dengan Terjadinya Diare Di Desa Pacet Kecamatan Pacet Kabupaten Mojokerto - Veryudha Eka P; Lutfi Wahyuni; Indria Kusuma Putri (Akademi Keperawatan Dharma Husada Kediri, 2015)
Complementary feeding (MP-ASI) was food and beverage contain of nutrients, which gave to infants or children age 6-24 months in order to meet the nutritional needs in addition to breast milk. The incidence of diarrhea in infants can be caused due to errors in feeding, where the baby has been feed than breast milk before the age of 6 months. This study aimed to analyze the relationship between the give complementary feeding in baby age 0-6 months with incidence diarrhea at the Pacet Village, Pacet District, Mojokerto. The research of the population has been taken from all baby 0-6 months at the Pacet Village, Pacet District, Mojokerto. And got the sample from 42 respondents with techniq of gotten the sample was Total Sampling. That was calling a retrospective research. Meanwhile processing data analysis was using coding, scoring, tabulating, and cross tabulation. Based on the result, it was showing that A Corellation of Giving Complementary Feeds (MP- ASI) to baby 0-6 months with incidence diarrhea in Pacet Village Pacet District Mojokerto. Feeding companion early breastfeeding can cause interference with absorption in the intestine due to the baby's digestive system is less than 6 months old and has not been perfect. Malabsorption that occurs will cause osmotic pressure in intestinal cavity increases resulting in a shift of water and electrolytes into gut cavity would which result diarrhea. Keywords: breast milk, baby 0-6 months, the incidence of diarrhea